Assessing heat stress risk to inform urban heat adaptation. A method applied in the Friuli Venezia Giulia region, Italy - Longato, Davide; Romanato, Nicola; Maragno, Denis (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Urban areas usually experience higher temperatures than their surroundings, especially due to impervious surfaces that absorb and re-emit solar radiation. This phenomenon is called urban heat island and occurs mainly at night. People living in urban settings are therefore particularly exposed to potential heat-related health problems caused during the hot season due to prolonged thermal discomfort conditions. This situation is likely to worsen in the future due to climate change, possibly resulting in increased health costs and socio-ecological inequalities. The socio-demographic structure of the population is key in determining the vulnerability of the population to heat stress conditions, with the weakest and most socially and economically disadvantaged being the most vulnerable. To support more targeted adaptation interventions to improve urban resilience and reduce people’s heat-related risks, this study develops a heat stress index that combines hazard, exposure, and vulnerability factors. The index is applied to the urban areas of the Friuli Venezia Giulia region (Italy), making it possible to identify risk hotspots that may be prioritized for reducing risk. The factors that contribute to determining the final risk condition are analyzed and discussed, together with the possible uses of the approach to support climate adaptation planning decisions at different scales and the risk mitigation solutions that may be implemented to this aim.